2009
DOI: 10.1073/pnas.0900433106
|View full text |Cite
|
Sign up to set email alerts
|

Dinuclear nickel complexes modeling the structure and function of the acetyl CoA synthase active site

Abstract: acetylthioester formation ͉ dinuclear nickel-site model ͉ N2S2 ligand ͉ nickel acyl complex A cetyl-CoA synthase/CO dehydrogenase (ACS/CODH), a bifunctional metalloenzyme found in acetogenic, methanogenic, and sulfate-reducing bacteria, has the important function of fixing CO and CO 2 in the global carbon cycle (1-3). Whereas CODH catalyzes the reversible conversion of CO 2 to CO, ACS assembles acetyl-CoA from CO, CoA, and a methyl moiety that is derived from the methylcobalamin of the corrinoid iron-sulfur pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 39 publications
3
45
0
Order By: Relevance
“…Where these electrons reside on the A-cluster is uncertain; indeed the location of these two electrons has been a decade-old puzzle that has not been resolved. One possibility is that both electrons localize on Ni p II to afford a d 10 Ni p 0 species [56 - 59]. Alternatively, one electron may localize on Ni p II and the other on the [Fe 4 S 4 ] 2+ cluster to afford a {Ni p I :[Fe 4 S 4 ] 1+ } spin-coupled structure.…”
Section: 4 Evidence For M-m Bonds In Metalloenzymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Where these electrons reside on the A-cluster is uncertain; indeed the location of these two electrons has been a decade-old puzzle that has not been resolved. One possibility is that both electrons localize on Ni p II to afford a d 10 Ni p 0 species [56 - 59]. Alternatively, one electron may localize on Ni p II and the other on the [Fe 4 S 4 ] 2+ cluster to afford a {Ni p I :[Fe 4 S 4 ] 1+ } spin-coupled structure.…”
Section: 4 Evidence For M-m Bonds In Metalloenzymesmentioning
confidence: 99%
“…Tatsumi, Rauchfuss, Riordan and others have synthesized A-cluster model complexes with two Ni ions and bridging dithiolates [59, 63 - 66], reminiscent of the Hase model compounds (Figure 6, top). These [Ni 0 Ni II ] compounds show flexible Ni-S 2 -Ni hinge angles, ranging from ca .…”
Section: 4 Evidence For M-m Bonds In Metalloenzymesmentioning
confidence: 99%
“…5e, that can be methylated by methyl-cobaloxime, and that can further react with CO to form an acetylthioester compound similar to acetyl-CoA. 51,52 In these studies, the compound Ni(dadt Et )Ni(Me)(SDmp), where dadt Et stands for N , N ′-diethyl-3,7-diazanonane-1,9-dithiolate and Dmp for 2,6-dimesitylphenyl, was synthesized as a Ni II –Ni I complex. It had a S = 1/2 EPR signal ( g x , y , z = 2.62, 2.12, 2.00), could be methylated and then react with CO.…”
Section: (Iv) Non-enzymatic Inorganic Compounds That Catalyze Reactimentioning
confidence: 99%
“…It has been shown that the presence of a CO ligand in the Ni(0) compound (bis(2-diphenylphosphinoethyl)phenylphosphine)-NiCO prevents methylation by methylcobaloxime (55). And, in recent studies on a binuclear Ni(II)-Ni(II) complex bearing methyl and thiol ligands, it was found that thioester formation, initiated by addition of CO, takes place as a single turnover process because of the concomitant formation of an inactive Ni(0)-carbonyl complex that does not react further with methylcobaloxime (56). This was interpreted to indicate that CO addition to Ni p in ACS must be strictly regulated to prevent the formation of such inactive Ni(0)-CO species.…”
Section: Mechanism Of Acetyl C-c Bond Fragmentationmentioning
confidence: 99%